Quantitative chemical risk assessment for mixtures: Application to alkylphenol mixtures and phthalate mixtures in tap and bottled water. (July 2022) - Penserini, Luca; Cantoni, Beatrice; Vries, Dirk; Turolla, Andrea; Smeets, Patrick W.M.H.; Bokkers, Bas G.H.; Antonelli, Manuela
Graphical abstract: Highlights: Quantitative chemical risk assessment for contaminants mixtures (QCRAMIX ) was created. Contaminants' mixtures risk comparison between bottled and tap water was performed. Alkylphenols and phthalates cause a non-negligible health risk in drinking water. Total drinking water consumption and source type differ substantially worldwide. Drinking water consumer behaviour considerably affects risk depending on contaminants. Abstract: The occurrence and hazard risks of mixtures of Contaminants of Emerging Concern (CECs) in drinking water (DW) lead to serious consideration regarding the possible impacts on public health. Consequently, there is ongoing research, development and empowerment of risk assessment procedures to get more toxicological insight. For instance, alkylphenols and phthalates have been frequently reported to be present both in bottled and tap water, affecting different human endpoints. Currently, deterministic chemical risk assessment (CRA) is used to evaluate the compounds' mixture health risk. However, CRA deals just qualitatively with sources of uncertainty, which may lead to erroneous assessment of risks. Here, a new procedure for quantitative chemical risk assessment of CEC mixtures (QCRAMIX ) is proposed. Its potential is illustrated by a case study where the risks related to the presence of mixtures of alkylphenols or phthalates in tap versus bottled DW are compared. Uncertainties in both exposure and hazard assessment steps of the procedure are included to calculate a probabilistic mixture Benchmark Quotient (BQMIX ). The QCRAMIX procedure highlighted the non-negligible health risks posed by those compounds in both DW sources based on overall water consumption. In fact, DW consumers' behaviour in 13 different countries, in terms of total DW consumption and fraction of bottled and tap water consumed, were considered to evaluate the influence on health risk. For alkylphenols, the total water consumption was found to be the most relevant factor in increasing the health risk, while for phthalates the risk was found to be mainly influenced by the percentage of bottled water consumed. Hence, the proposed QCRAMIX procedure can be a valuable tool for prioritization of CECs to be included in DW regulations which aim to minimize the overall risk, accounting for actual DW consumption.